Claudina-3 e Claudina- 4, potenciais marcadores de agressividade no carcinoma endometrial Tipo I - Tonon, Ângela Favorito Santarém [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Carcinoma of the Endometrium is a malignant epithelial tumor which affects pre, peri and post-menopausal women. It is classified into two major groups, according to endocrine, metabolic risk factors and morphological differences: Type I (endometrioid) and Type II (non-endometrioid). Type I accounts for 90% of all endometrial carcinomas and its pathogenesis is linked to excessive estrogen exposure. The Type II is less common, with poorly defined predisposing factors. The most important symptom of endometrial carcinoma is postmenopausal bleeding. Diagnosis is achieved through histological evidence, in association with imaging and laboratorial exams. Treatment is primarily surgical. The most important prognostic factor is the presence or absence of metastases in regional lymph nodes. Bio and tissue markers that indicate worse prognosis are the focus of current research. This study examined the immunoexpression of claudin-3 (CLDN3) and claudin-4 (CLDN4) in endometrial carcinomas Type I and Type II, and their relation to proliferative and atrophic endometrium, clinical and pathological features, hormonal status, proliferation index and p53 expression, in an attempt to establish the importance of these proteins in tumor progression and aggressiveness and their prognostic value. Seventy-nine cases of endometrial carcinoma were studied and compared with 74 normal endometria. The immunoexpression of CLDNs 3 and 4, estrogen receptor, progesterone receptor, cell proliferation index (Ki67) and p53 were all evaluated by immunohistochemistry. Observation verified that the pattern of membrane staining for CLDN3 was diffuse in carcinomas compared with normal endometrium which presented a focal pattern. The number of cells stained with CLDN3 was lower in Type I carcinomas, while staining intensity was greater. Analysis verified that 25% of cases with high expression of CLDN4 and Ki-67 developed metastasis, while 33% of cases with greater CLDN4 staining ...

O Carcinoma de Endométrio é a neoplasia epitelial maligna que acomete mulheres no pré, pós e peri -menopausa. Segundo diferenças endócrinas, metabólicas, fatores de risco e morfologia é classificado em dois grandes grupos: Tipo I (endometrióide) e Tipo II (não endometrióide). O Tipo I perfaz 90 % dos carcinomas de endométrio e sua patogenia esta ligada a exposição excessiva ao estrógeno. O Tipo II é incomum, com fatores predisponentes menos conhecidos. O sintoma mais relevante do carcinoma de endométrio é o sangramento pós-menopausa. Seu diagnóstico é feito pela comprovação histológica, associada aos exames de imagem e laboratoriais. Seu tratamento é fundamentalmente cirúrgico. O fator prognóstico mais importante é a presença ou ausência de metástase nos linfonodos regionais. Atualmente, buscam-se marcadores biológicos e teciduais que indiquem pior prognóstico. Este trabalho verificou a imunoexpressão da claudina-3 (CLDN3) e claudina-4 (CLDN4) nos carcinomas de endométrio Tipo I e Tipo II, relacionando-as com endométrio proliferativo e atrófico, aspectos clínicos, anatomopatológicos, perfil hormonal, índice de proliferação celular e expressão da p53, na tentativa de estabelecer a importância destas proteínas na progressão e agressividade tumoral e o seu valor prognóstico. Foram estudados 79 casos de carcinoma de endométrio e comparados com 74 endométrios normais. Avaliou-se a imunoexpressão das CLDNs 3 e 4, receptor estrogênico, receptor de progesterona, índice de proliferação celular (Ki67) e p53, pela técnica de imunoistoquímica. Observou-se que o padrão de coloração da membrana para CLDN3 se mostrou difuso nos carcinomas, quando comparado com os endométrios normais que exibiu padrão focal. O número de células marcadas com CLDN3 estava diminuído nos carcinomas Tipo I, porém com intensidade aumentada. Nesta análise foi possível verificar que ...
Keywords: Endometrio - Cancer; Metastase; Imuno-histoquímica; Marcadores biologicos; Endometrium Cancer